Positive pole piece, secondary battery and electronic device

By adding first compounds such as vinyl phosphate to the positive electrode material layer of the lithium-ion battery, the problem of excessive residual alkali content of the positive electrode material layer of the ternary material is solved, and the high-temperature cycling performance and the improvement of thermal safety performance are achieved.

CN119673957AActive Publication Date: 2025-03-21NINGDE AMPEREX TECHNOLOGY LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411783443.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-21
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The residual alkali content of the ternary material positive electrode layer in lithium-ion batteries is too high, resulting in high-temperature gas production and interface bonding, reducing cycling performance.

Method used

The first compound such as vinyl phosphate is added to the positive electrode material layer, and the residual alkali is neutralized through the presence of characteristic peaks of infrared spectrum, the oxidation potential is reduced, the film formation is promoted, and the side reaction is reduced.

Benefits of technology

Effectively reduce the residual alkali content of the positive electrode material layer, improve high-temperature cycling performance, take into account low-temperature performance and impedance performance, improve the thermal stability of the positive electrode interface, and improve the thermal safety performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673957A_ABST
    Figure CN119673957A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a secondary battery and an electronic device, the positive pole piece comprises a positive current collector and a positive material layer located on at least one surface of the positive current collector, the positive material layer comprises a positive active material and a first compound, the first compound comprises at least one of vinyl phosphate, allyl phosphate, vinylene phosphate, diallyl phosphate, styrene phosphate, diphenyl phosphate or stilbene phosphate, and an infrared spectrogram of the positive electrode material layer has infrared characteristic peaks at any two of 1150cm <-1 > + / -10cm <-1 >, 1085cm <-1 > + / -10cm <-1 >, 1600cm <-1 > + / -10cm <-1 >, 1640cm <-1 > + / -10cm <-1 > or 1500cm <-1 > + / -10cm <-1 >. Through the arrangement, the high-temperature cycle performance and the thermal safety performance of the secondary battery can be improved, and the low-temperature performance and the impedance performance are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet, a secondary battery and an electronic device. Background Art

[0002] Lithium-ion batteries have significant advantages such as high energy density, miniaturization and light weight, and are widely used in mobile phones, laptops, tablets, drones, electric vehicles, power tools, power storage systems, etc.

[0003] Ternary materials such as lithium nickel cobalt manganese oxide are often used as positive electrode active materials in lithium-ion batteries. However, when ternary materials are used as positive electrode active materials, the production process of the ternary materials themselves can easily lead to excessive residual alkali content in the positive electrode material layer. During the cycle process, the lithium-ion battery produces gas at high temperature, and interfacial bonding occurs between the positive electrode plate and the diaphragm, which reduces the initial efficiency of the lithium-ion battery and thus leads to a decrease in cycle performance. Summary of the invention

[0004] The purpose of the present application is to provide a positive electrode plate, a secondary battery and an electronic device to reduce the residual alkali content on the surface of the positive electrode material layer, improve high-temperature gas production, thereby enhancing the high-temperature cycle performance of the secondary battery, taking into account the low-temperature and impedance performance, and improving the thermal safety performance of the secondary battery.

[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material and a first compound, the first compound includes at least one of vinyl phosphate, allyl phosphate, vinylidene phosphate, diallyl phosphate, styrene phosphate, diphenyl phosphate or distyrene phosphate, and the infrared spectrum of the positive electrode material layer is at 1150cm -1 ±10cm -1 , and 1085cm -1 ±10cm -1 、1600cm -1 ±10cm -1 、1640cm -1 ±10cm -1 or 1500cm -1 ±10cm -1There are infrared characteristic peaks at any two places in the positive electrode material layer. Through the above-mentioned setting, the residual alkali can be neutralized to reduce the residual alkali content on the surface of the positive electrode material layer and improve high-temperature gas production; and the oxidation potential of the first compound is relatively low at about 3.7V, which can promote positive electrode film formation and reduce the risk of transition metal dissolution and electrolyte oxidation; in addition, the C=C unsaturated bond in the first compound can form a film at the negative electrode, reduce the side reaction between the negative electrode plate and the electrolyte, and improve the cycle performance of the secondary battery. When the first compound is included in the positive electrode material layer, the high-temperature cycle performance of the secondary battery can be improved, taking into account the low-temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0007] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage of the first compound is B, 0.1%≤B≤3%; preferably, 0.1%≤B≤1%. By adjusting the mass percentage of the first compound B within the above range, it is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improve the thermal stability of the positive electrode interface, and improve the thermal safety performance of the secondary battery.

[0008] In some embodiments of the present application, the positive electrode active material includes LiNi x Co y M 1-x-y O2, 0.6≤x≤1.0, 0≤y≤0.4, M is Al or Mn. In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the lithium nickel cobalt manganese oxide includes a metal element M1, and the metal element M1 includes at least one of Al, Zr, Mg, Ba or Ti. In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt aluminum oxide, and the lithium nickel cobalt aluminum oxide includes a metal element M2, and the metal element M2 includes at least one of Zr, Mg, Ba or Ti. In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, and the lithium nickel cobalt manganese oxide includes a metal element M1, and the metal element M1 includes at least one of Al, Zr, Mg, Ba or Ti; the lithium nickel cobalt aluminum oxide includes a metal element M2, and the metal element M2 includes at least one of Zr, Mg, Ba or Ti. By selecting the positive electrode active material within the above range, it is beneficial to further improve the thermal stability and electrochemical performance of the positive electrode active material. The positive electrode active material within the scope of this application is used in combination with the first compound, which is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0009] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage of the positive electrode active material is A; the mass percentage of the first compound is B, and A, x and B satisfy: B = k × A × x, 93% ≤ A ≤ 95.9%, 0.6 ≤ x ≤ 0.9, 0.001792 ≤ k ≤ 0.03475. When the above relationship is satisfied between A, x and B, and the values ​​of A, x and k are regulated within the above range, it is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery. While taking into account the high energy density of the secondary battery, the structural stability of the positive electrode sheet is further improved.

[0010] The second aspect of the present application provides a secondary battery, which includes a negative electrode sheet, a separator, an electrolyte, and a positive electrode sheet in any of the above embodiments. The secondary battery of the present application has good high-temperature cycle performance and thermal safety performance, and takes into account low-temperature performance and impedance performance.

[0011] In some embodiments of the present application, the electrolyte includes a second compound, the second compound includes at least one of a cyclic sulfate compound or a cyclic carbonate compound, the cyclic sulfate compound includes at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate, and the cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate or fluoroethylene carbonate; based on the mass of the electrolyte, the mass percentage of the second compound is C, 0.05%≤C≤3%. By adding the above-mentioned type of second compound to the electrolyte and regulating the mass percentage C of the second compound within the above range, the first compound and the second compound work synergistically to further improve the high temperature storage and cycle performance of the secondary battery.

[0012] In some embodiments of the present application, the electrolyte includes a third compound, the third compound includes at least one of methylene disulfonate, vinylene carbonate, ethyl methyl carbonate or methyl propyl carbonate, and the mass percentage of the third compound is D based on the mass of the electrolyte, 0.05%≤D≤2%. By adding the third compound of the above type to the electrolyte and regulating the mass percentage D of the third compound within the above range, the high temperature cycle performance of the secondary battery is further improved, the low temperature and impedance performance are taken into account, and the thermal safety performance of the secondary battery is improved.

[0013] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.

[0014] Beneficial effects of this application:

[0015] The present application provides a positive electrode sheet, a secondary battery and an electronic device, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, wherein the positive electrode material layer comprises a positive electrode active material and a first compound, wherein the first compound comprises at least one of vinyl phosphate, allyl phosphate, vinylidene phosphate, diallyl phosphate, styrene phosphate, diphenyl phosphate or distyrene phosphate, and the infrared spectrum of the positive electrode material layer is at 1150cm -1 ±10cm -1 , and 1085cm -1 ±10cm -1 、1600cm -1 ±10cm -1 、1640cm -1 ±10cm -1 or 1500cm -1 ±10cm -1 There are infrared characteristic peaks at any two places in the positive electrode material layer. Through the above-mentioned setting, the residual alkali can be neutralized to reduce the residual alkali content on the surface of the positive electrode material layer and improve high-temperature gas production; and the oxidation potential of the first compound is relatively low at about 3.7V, which can promote positive electrode film formation and reduce the risk of transition metal dissolution and electrolyte oxidation; in addition, the C=C unsaturated bond in the first compound can form a film at the negative electrode, reduce the side reaction between the negative electrode plate and the electrolyte, and improve the cycle performance of the secondary battery. When the first compound is included in the positive electrode material layer, the high-temperature cycle performance of the secondary battery can be improved, taking into account the low-temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0016] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0018] Figure 1 This is the infrared spectrum of diphenyl phosphate. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0020] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0021] Nickel-cobalt-manganese ternary positive electrode materials have been widely used in the fields of batteries for computers, communications and consumer electronic products (3C electronic products) and power batteries due to their advantages of low cost, high specific capacity and stable cycle performance. In lithium-ion battery positive electrode materials, replacing high-voltage lithium cobalt oxide with some high-voltage ternary materials can reduce the cost of lithium battery positive electrodes, but the ternary materials have a high pH value and high residual alkali on the surface of the materials, which makes lithium-ion batteries easy to swell, and have high requirements for the manufacturing process and environment, making processing difficult; in addition, the cycle stability deteriorates at high voltages above 4.4V. Therefore, there is an urgent need for a solution that can solve the above-mentioned technical problems. Based on this, the present application provides a positive electrode plate, a secondary battery and an electronic device that can effectively improve the high-temperature cycle performance and thermal safety performance of secondary batteries, especially the ternary positive electrode material system, while taking into account low temperature and impedance performance. The specific technical solution is as follows:

[0022] The first aspect of the present application provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material and a first compound, the first compound includes at least one of vinyl phosphate, allyl phosphate, vinylidene phosphate, diallyl phosphate, styrene phosphate, diphenyl phosphate or distyrene phosphate, and the infrared spectrum of the positive electrode material layer is at 1150cm -1 ±10cm -1 , and 1085cm -1 ±10cm -1 、1600cm -1 ±10cm -1 、1640cm -1 ±10cm -1 or 1500cm -1 ±10cm -1 There are infrared characteristic peaks at any two locations.

[0023] The inventors have found that when the first compound of the present application is added to the positive electrode material layer, the infrared spectrum of the positive electrode material layer has a wavelength of 1150cm -1 ±10cm -1 , and 1085cm -1 ±10cm -1 、1600cm -1 ±10cm -1 、1640cm -1 ±10cm -1 or 1500cm -1±10cm -1 There are infrared characteristic peaks at any two locations. Exemplarily, Figure 1 This is the infrared spectrum of diphenyl phosphate. This substance has a wavelength of 1150 cm -1 、1600cm -1 and 1490cm -1 There are infrared characteristic peaks at, which may correspond to the phosphate group and the C=C group. When the first compound of the present application is added to the positive electrode material layer, the positive electrode material layer includes the phosphate group and the C=C group, which can neutralize the residual alkali to reduce the residual alkali content on the surface of the positive electrode material layer and improve the high-temperature gas production; and the oxidation potential of the first compound is relatively low at about 3.7V, which can promote the positive electrode film formation and reduce the risk of transition metal dissolution and electrolyte oxidation; in addition, the C=C unsaturated bond in the first compound can form a film at the negative electrode, reduce the side reaction between the negative electrode plate and the electrolyte, improve the cycle performance of the secondary battery, and improve the first efficiency of the secondary battery. When the first compound is included in the positive electrode material layer, the high-temperature cycle performance of the secondary battery can be improved, taking into account the low-temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0024] The above-mentioned "negative electrode material layer located on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be located on one surface of the positive electrode current collector along its thickness direction, or on two surfaces of the positive electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. This application is not particularly limited, as long as the purpose of this application can be achieved.

[0025] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage of the first compound is B, 0.1%≤B≤3%; preferably, 0.1%≤B≤1%. For example, the value of B can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3% or a range consisting of any two of these values. By regulating the mass percentage B of the first compound within the above range, it is beneficial to neutralize the residual alkali to reduce the residual alkali content on the surface of the positive electrode material layer and improve high-temperature gas production; and the oxidation potential of the first compound is relatively low at about 3.7V, which can promote positive electrode film formation and reduce the risk of transition metal dissolution and electrolyte oxidation; in addition, the C=C unsaturation in the first compound can form a film at the negative electrode, reduce the side reaction between the negative electrode plate and the electrolyte, and improve the cycle performance of the secondary battery. When the first compound within the above content range is added to the positive electrode material layer, it is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface and improving the thermal safety performance of the secondary battery.

[0026] In some embodiments of the present application, the positive electrode active material includes LiNi x Co y M 1-x-y O2, 0.6≤x≤1.0, 0≤y≤0.4, M is Al or Mn. For example, the value of x can be 0.6, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1 or a range consisting of any two of them; the value of y can be 0, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4 or a range consisting of any two of them. When the positive electrode active material within the above range is selected, the positive electrode active material has a higher theoretical specific capacity and has good structural stability and thermal stability during the charge and discharge cycle. The positive electrode active material within the scope of this application is used in combination with the first compound, which is beneficial to improving the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface and improving the thermal safety performance of the secondary battery.

[0027] In some embodiments of the present application, based on the mass of the positive electrode material layer, the mass percentage of the positive electrode active material is A, and the mass percentage of the first compound is B; A, x and B satisfy: B = k × A × x, 93% ≤ A ≤ 95.9%, 0.6 ≤ x ≤ 0.9, 0.001792 ≤ k ≤ 0.03475. For example, the value of A can be 93%, 93.2%, 93.5%, 93.8%, 94%, 94.2%, 94.5%, 94.8%, 95%, 95.2%, 95.5%, 95.8%, 95.9% or a range consisting of any two of the values; the value of x can be 0.6, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0. 85, 0.88, 0.9 or a range consisting of any two of them; the value of k can be 0.001792, 0.0018, 0.002, 0.005, 0.008, 0.01, 0.012, 0.015, 0.018, 0.02, 0.022, 0.025, 0.028, 0.03, 0.032, 0.34, 0.03475 or a range consisting of any two of them. When the above relationship is satisfied between A, x and B, and the values ​​of A, x and k are regulated within the above range, the positive electrode material layer includes a positive electrode active material containing a high Ni content, and the first compound is matched with the positive electrode active material containing a high Ni content, which can neutralize the residual alkali to reduce the residual alkali content on the surface of the positive electrode material layer and improve high-temperature gas production; and the oxidation potential of the first compound is relatively low at about 3.7V, which can promote positive electrode film formation and reduce the risk of transition metal dissolution and electrolyte oxidation; in addition, the C=C unsaturation in the first compound can form a film at the negative electrode, reduce the side reaction between the negative electrode plate and the electrolyte, and improve the cycle performance of the secondary battery. When the first compound within the above content range is added to the positive electrode material layer, it is beneficial to improve the high-temperature cycle performance of the secondary battery, taking into account the low-temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery. While taking into account the high energy density of the secondary battery, the structural stability of the positive electrode plate is further improved.

[0028] In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the lithium nickel cobalt manganese oxide includes a metal element M1, and the metal element M1 includes at least one of Al, Zr, Mg, Ba or Ti. By regulating the type of M1 within the above range, it is beneficial to further improve the thermal stability and electrochemical performance of the positive electrode active material. The positive electrode active material within the scope of the present application is used in combination with the first compound, which is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0029] In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt aluminum oxide, and the lithium nickel cobalt aluminum oxide includes a metal element M2, and the metal element M2 includes at least one of Zr, Mg, Ba or Ti. By regulating the type of M2 within the above range, it is beneficial to further improve the thermal stability and electrochemical performance of the positive electrode active material. The positive electrode active material within the scope of the present application is used in combination with the first compound, which is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0030] In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide, the lithium nickel cobalt manganese oxide includes a metal element M1, and the metal element M1 includes at least one of Al, Zr, Mg, Ba or Ti; the lithium nickel cobalt aluminum oxide includes a metal element M2, and the metal element M2 includes at least one of Zr, Mg, Ba or Ti. By regulating the types of M1 and M2 within the above range, it is beneficial to further improve the thermal stability and electrochemical performance of the positive electrode active material. The positive electrode active material within the scope of the present application is used in combination with the first compound, which is beneficial to improve the high temperature cycle performance of the secondary battery, taking into account the low temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, and improving the thermal safety performance of the secondary battery.

[0031] In the present application, lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide with different Ni element contents can be purchased, and combined with the test method of "A, B and x test" of the present application, lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide with the required Ni element content can be selected.

[0032] The present application does not have any special restrictions on the doping amount of the metal element M1, as long as the purpose of the present application can be achieved. For example, based on the residual mass of the metal element M1 removed from the nickel cobalt manganese oxide, the mass percentage of the metal element M1 is 0.002% to 0.028%, that is, the doping amount of the metal element M1 is 0.002% to 0.028%. The present application does not have any special restrictions on the doping amount of the metal element M2, as long as the purpose of the present application can be achieved. For example, based on the residual mass of the metal element M2 removed from the nickel cobalt aluminum oxide, the mass percentage of the metal element M2 is 0.001% to 0.02%, that is, the doping amount of the metal element M2 is 0.001% to 0.02%.

[0033] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector), etc. In the present application, the positive electrode material layer also includes a positive electrode binder and a conductive agent. The present application has no particular restrictions on the type of positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The present application has no particular restrictions on the type of conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNT), carbon fibers, flake graphite, Ketjen black or graphene. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The carbon fiber may include, but is not limited to, vapor grown carbon fiber (VGCF) and / or nano carbon fiber.

[0034] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes but is not limited to the following steps: (1) the positive electrode active material, the first compound, the positive electrode binder and the conductive agent are mixed in a certain mass ratio and then added to a solvent to prepare a positive electrode slurry; (2) the positive electrode slurry is coated on one surface of the positive electrode collector, and after drying, a positive electrode sheet with a single-sided positive electrode material layer is obtained; (3) the above steps are repeated on the other surface of the positive electrode collector to obtain a positive electrode sheet with a double-sided positive electrode material layer; (4) the positive electrode sheet is obtained after cold pressing, cutting and slitting.

[0035] In the present application, the mass percentage B of the first compound in the positive electrode material layer and the mass percentage A of the positive electrode active material in the positive electrode material layer can be regulated by adjusting the mass ratio of the positive electrode active material, the first compound, the positive electrode binder and the conductive agent. The present application has no special restrictions on the solvent and solid content used in the positive electrode slurry in the above step (1), as long as the purpose of the present application can be achieved. The present application has no special restrictions on the drying temperature and time in the above step (2), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the process parameters of cold pressing, cutting and slitting in the above step (4), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the size of the above-mentioned positive electrode sheet, as long as the purpose of the present application can be achieved.

[0036] The second aspect of the present application provides a secondary battery, which includes a negative electrode sheet, a separator, an electrolyte, and a positive electrode sheet in any of the above embodiments. The secondary battery of the present application has good high-temperature cycle performance and thermal safety performance, and takes into account low-temperature performance and impedance performance.

[0037] In some embodiments of the present application, the electrolyte includes a second compound, the second compound includes at least one of a cyclic sulfate compound or a cyclic carbonate compound, the cyclic sulfate compound includes at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate, and the cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate or fluoroethylene carbonate; based on the mass of the electrolyte, the mass percentage of the second compound is C, 0.05%≤C≤3%. For example, the value of C can be 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3% or a range consisting of any two of the values. By adding the above-mentioned type of second compound to the electrolyte and regulating the mass percentage C of the second compound within the above-mentioned range, the first compound and the second compound act synergistically, which is beneficial to improving the thermal stability of the electrolyte, reducing the risk of gas generation by electrolyte decomposition under high temperature conditions, and improving the stability of the solid electrolyte interface (SEI) film, further improving the high-temperature storage and cycle performance of the secondary battery, taking into account the low-temperature performance and impedance performance, and effectively improving the thermal stability of the positive electrode interface, thereby improving the thermal safety performance of the secondary battery.

[0038] In some embodiments of the present application, the electrolyte includes a third compound, the third compound includes at least one of methylene disulfonate, vinylene carbonate, ethyl methyl carbonate or methyl propyl carbonate, and the mass percentage of the third compound is D based on the mass of the electrolyte, 0.05%≤D≤2%. For example, the value of D can be 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2% or a range consisting of any two of the values. By adding the third compound of the above type to the electrolyte and regulating the mass percentage D of the third compound within the above range, it is beneficial to form a more stable SEI film during the charge and discharge process of the secondary battery, the first compound and the third compound work synergistically, and the third compound has good electrochemical stability, thereby further improving the high temperature cycle performance of the secondary battery, taking into account low temperature and impedance performance, and improving the thermal safety performance of the secondary battery.

[0039] In the present application, the electrolyte also includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 1% to 15%.

[0040] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.

[0041] The carbonate compound may include but is not limited to at least one of a chain carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), and ethyl propyl carbonate (EPC). The fluorinated carbonate compound may include but is not limited to at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compounds may include but are not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methylcyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no particular limitation on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 80% to 99%.

[0042] This application has no particular limitation on the negative electrode sheet, as long as the purpose of this application can be achieved. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on both surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or a partial area of the surface of the negative electrode current collector. This application has no particular limitation, as long as the purpose of this application can be achieved. This application has no particular limitation on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, the negative electrode current collector can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as lithium-copper composite current collector, carbon-copper composite current collector, nickel-copper composite current collector, titanium-copper composite current collector, etc.). The negative electrode material layer of this application includes a negative electrode active material. This application has no particular limitation on the type of the negative electrode active material, as long as the purpose of this application can be achieved. For example, the negative electrode active material can include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0 < x ≤ 2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate Li4Ti5O with spinel structure 12 , Li-Al alloy or at least one of metallic lithium. In this application, there is no particular limitation on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of this application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 20 μm, and the thickness of the negative electrode material layer is 30 μm to 130 μm. Optionally, the negative electrode material layer may further include a conductive agent and a negative electrode binder. This application has no particular limitation on the type of the conductive agent in the negative electrode material layer, as long as the purpose of this application can be achieved. For example, the conductive agent can be of the same type as the conductive agent in the above positive electrode material layer. This application has no particular limitation on the type of the negative electrode binder in the negative electrode material layer, as long as the purpose of this application can be achieved. For example, the negative electrode binder can be of the same type as the positive electrode binder in the above positive electrode material layer. Optionally, the negative electrode material layer further includes a thickening agent. This application has no particular limitation on the type of the thickening agent, as long as the purpose of this application can be achieved. For example, the thickening agent can include at least one of carboxymethyl cellulose or sodium carboxymethyl cellulose. This application has no particular limitation on the mass ratio of the negative electrode active material, conductive agent, binder and thickening agent in the negative electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of this application can be achieved.

[0043] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane, or a spun membrane.

[0044] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0045] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0046] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0047] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.

[0048] The secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0049] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0050] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0051] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.

[0052] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0053] Example

[0054] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0055] Test methods and equipment:

[0056] Infrared spectrum test:

[0057] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, the electrolyte was collected by centrifugation, and the lithium-ion battery was disassembled to obtain the positive electrode sheet. The positive electrode sheet was soaked in 10mL of dimethyl carbonate (DMC) for 30min and mixed with the electrolyte collected by centrifugation. The positive electrode sheet was then baked at 100℃ for 2h for standby use. The positive electrode material layer on the positive electrode sheet was scraped off and the powder of the positive electrode material layer was collected.

[0058] Using an infrared spectrometer (model: Nicolet iS50), potassium bromide (KBr) tablet method and liquid film method were used to test the collected liquid and solid samples respectively to obtain the infrared spectrum of the positive electrode material layer. 500 mg of KBr and 10 mg of positive electrode material layer powder were ground in a mortar to obtain a mixed material. The mixed material was loaded into a pressure mold and pressurized to 20 MPa. After maintaining for 10 seconds, the pressure was released to obtain a disc; the disc was taken out and the infrared spectrum of the solid sample was tested using an infrared spectrometer. The window was cleaned with acetone, and the collected liquid sample was evenly applied to the window for testing, and the infrared spectrum of the liquid sample was tested using an infrared spectrometer. The original spectra of the obtained solid sample and liquid sample were pre-processed and then merged to obtain the infrared spectrum of the positive electrode material layer.

[0059] Tests of A, B and x:

[0060] A's test:

[0061] (1) Take the positive electrode sheet cleaned with DMC and use a 1540.25mm 2 Punching the double-sided material layer area of ​​the positive electrode plate and the positive electrode current collector aluminum foil with a punching die; the number of double-sided material layer discs is 3 pieces, and the number of aluminum foil is 1 piece;

[0062] (2) Weigh the mass of weighing bottle A and filter membrane B, recorded as M0; weigh the weight of a single piece of aluminum foil, recorded as M1; use a 250mL conical flask to peel off the weight of three punched positive electrode sheets, recorded as M2;

[0063] (3) Add about 50 mL of concentrated hydrochloric acid into a conical flask;

[0064] (4) Place the conical flask on a flat heater to heat and digest. When it is almost dry, add appropriate amount of water to continue. Stop heating after boiling for 15 minutes and remove it to cool.

[0065] (5) Filter the digested solution with a vacuum filter and rinse the residue in the conical flask with deionized water 3 to 4 times until it becomes colorless;

[0066] (6) Add 50 mL of concentrated hydrochloric acid to the conical flask containing the filter residue and continue digestion;

[0067] (7) Vacuum filter and rinse the residue with deionized water 3 to 4 times. Add a small amount of concentrated hydrochloric acid to the conical flask where the residue is retained. If it is colorless and transparent, it means that the components of the positive electrode active material have been completely digested and no further digestion is required. Otherwise, repeat steps (4) to (5) until the filtrate is transparent;

[0068] (8) Transfer the filter residue and filter membrane B to weighing bottle A. Be careful not to lose the mass of the filter residue. Place it in a vacuum drying oven at 85°C for more than 4 hours to ensure thorough drying. Then take out the weighing bottle and move it to a dryer to cool for half an hour. Then weigh the mass M3 of the dried filter residue, filter membrane and weighing bottle.

[0069] (9) Then the mass percentage of the positive electrode active material is A = (M3-M0) / (M2-M1×3).

[0070] B's test:

[0071] The content of the first compound in the liquid and solid samples collected after centrifugation is tested in the same manner as the infrared spectrum test step above.

[0072] Test for x:

[0073] The mass percentage of each metal element in the positive electrode material layer is tested by an energy dispersive X-ray spectrometer (EDS), and the molar percentage of the Ni element in the positive electrode active material can be obtained based on the mass percentage of the positive electrode active material in the positive electrode material layer obtained above, and then x can be calculated.

[0074] Test of component content in electrolyte:

[0075] The lithium-ion battery was discharged at a constant current of 0.5C to 2.8V and then disassembled, the electrolyte was collected, and the disassembled positive electrode sheet, negative electrode sheet, and separator were centrifuged. The liquid obtained after centrifugation was evenly mixed with the above electrolyte, and then tested using a gas chromatography-mass spectrometer (instrument model: Agilent 8890) and an ion chromatography (instrument model: AQUION ion chromatography) to obtain each component in the electrolyte and test its content.

[0076] First efficiency test:

[0077] The lithium-ion batteries in the embodiments and comparative examples were subjected to formation and capacity tests to compare the initial efficiency of the lithium-ion batteries. Test conditions: The lithium-ion batteries were first formed, and then charged at 80°C and 1.2Mpa for 300s at 0.3C constant current, then 270s at 1C constant current, and then 1980s at 1.5C constant current, and the charging capacity C1 was recorded; then at 45°C, the battery was charged to 4.4V at 0.5C constant current, and then charged to 0.05C at constant voltage, and after standing for 5 minutes, the battery was discharged to 3.0V at 0.5C, and the charging capacity C2 and initial discharge capacity D' of the lithium-ion battery were recorded.

[0078] The first efficiency of lithium-ion battery (%) = first discharge capacity / first charge capacity×100%=D' / (C1+C2)×100%.

[0079] 85℃, 4 hours high temperature storage test:

[0080] The lithium-ion batteries in the embodiments and comparative examples were subjected to a high-temperature storage test at 85°C for 4 hours. At room temperature of 25°C, the lithium-ion battery was charged to 4.4V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage and allowed to stand for 1 hour. The thickness, voltage and internal resistance of the lithium-ion battery were measured. The battery was charged to 4.4V at a constant current of 0.2C, and then charged to 0.05C at a constant voltage. After standing for 5 minutes, it was discharged to 3.0V at 0.2C, and the discharge capacity before storage was recorded; the lithium-ion battery was placed in a constant temperature box at 85°C, and allowed to stand for 4 hours. The thickness, voltage and internal resistance of the lithium-ion battery were measured at a high temperature of 85°C. After cooling to room temperature of 25°C, the battery was charged to 4.4V at a constant current of 0.2C, and then charged to 0.05C at a constant voltage. After standing for 5 minutes, it was discharged to 3.0V at 0.2C, and the discharge capacity after storage was recorded.

[0081] Thickness expansion rate at 85°C for 4 hours (%) = (thickness after storage - thickness before storage) / thickness before storage × 100%;

[0082] 85°C, 4 hours capacity retention rate (%) = discharge capacity after storage / discharge capacity before storage × 100%.

[0083] 60℃, 30 days high temperature storage test:

[0084] The lithium-ion batteries in the embodiments and comparative examples were subjected to a 60°C, 30-day high-temperature storage test. At room temperature 25°C, the lithium-ion battery was charged to 4.4V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage and allowed to stand for 1 hour. The thickness, voltage and internal resistance of the lithium-ion battery were measured. The battery was charged to 4.4V at a constant current of 0.2C, and then charged to 0.05C at a constant voltage. After standing for 5 minutes, it was discharged to 3.0V at 0.2C, and the discharge capacity before storage was recorded; the lithium-ion battery was placed in a 60°C constant temperature box, and after standing for 30 days, the thickness, voltage and internal resistance of the lithium-ion battery were measured at a high temperature of 60°C, cooled to room temperature 25°C, charged to 4.4V at a constant current of 0.2C, and then charged to 0.05C at a constant voltage. After standing for 5 minutes, it was discharged to 3.0V at 0.2C, and the discharge capacity after storage was recorded.

[0085] Thickness expansion rate at 60°C for 30 days (%) = (thickness after storage - thickness before storage) / thickness before storage × 100%;

[0086] Capacity retention rate at 60°C and 30 days (%) = discharge capacity after storage / discharge capacity before storage × 100%.

[0087] Hot box pass rate test of lithium-ion batteries:

[0088] The hot box test process is as follows:

[0089] (1) Adjust the furnace temperature to 25°C and let it stand for 5 minutes; (2) Charge with 0.2C DC to 3.0V; (3) Let it stand for 10 minutes; (4) Charge with 0.7C constant current to 4.4V and charge with 4.4V constant voltage to 0.05C; (5) Let it stand for 10 minutes.

[0090] Take photos before the test, measure the voltage and internal resistance of the lithium-ion battery, attach the temperature sensor to the surface of the lithium-ion battery, put the lithium-ion battery sample into the heating furnace, heat it to 130±2℃ at a rate of 5±2℃ / min and keep it for 60min, take photos after the test, measure the voltage and internal resistance of the lithium-ion battery. Each group tests 10 lithium-ion batteries. If the lithium-ion battery does not catch fire or explode, it means it has passed the hot box test.

[0091] Excessive release gas production test:

[0092] The voltage was tested online using a Xinwei machine, and the thickness of lithium-ion batteries was tested online using Yuanneng Technology's CBS1300. Under 25°C conditions, the lithium-ion batteries in the examples and comparative examples were discharged at a constant current of 0.05C to 3.0V and then left to stand for 5 minutes, then discharged at a constant current of 10mA to 0.1C and left to stand for 30 minutes, and then discharged at a constant current of 1mA to 0.1C and left to stand for 30 minutes. During the process, the voltage and thickness (Tx) were tested online every 30 seconds, and the initial thickness was recorded as T0. Then, the thickness expansion rate (Tx / T0) of the lithium-ion battery was calculated. The smaller the thickness expansion rate at the same voltage level, the better the SEI film formation uniformity of the secondary battery.

[0093] DC resistance (DCR) test:

[0094] At 10°C, charge the lithium-ion batteries in the examples and comparative examples to 4.4V at a constant current of 0.5C, and then charge to 0.05C at a constant voltage of 4.4V; let stand for 30 minutes. Then discharge at 0.1C for 10 seconds (take a point every 0.1 seconds and record the corresponding voltage value U1), and discharge at 1C for 360 seconds (take a point every 0.1 seconds and record the corresponding voltage value U2). Repeat the above charging and discharging steps 5 times. Among them, "1C" is the current value that completely discharges the capacity of the lithium-ion battery within 1 hour.

[0095] The DCR of lithium-ion batteries is calculated as follows:

[0096] DCR (mΩ)=(U2-U1) / (1C-0.1C).

[0097] The DCR in this application is the value at 50% state of charge (SOC).

[0098] Example 1-1

[0099] <Preparation of positive electrode sheet>

[0100] The positive electrode active material is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1O2), conductive carbon black (Super P), conductive carbon nanotubes (CNT), positive electrode binder polyvinylidene fluoride (PVDF) and the first compound vinyl phosphate are mixed in a mass ratio of 95.4:2:0.8:1.2:0.6, N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred and mixed to form a uniform positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried at 85°C to obtain a positive electrode sheet with a single-sided positive electrode material layer, and then the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. Then, after cold pressing, cutting, slitting, and drying at 85°C under vacuum conditions for 4h, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the coating weight of the positive electrode material layer during coating is 0.2419g / 1540.25mm 2 The compaction density of the positive electrode material layer after cold pressing is 3.4g / cm 3 Wherein, based on the mass of the positive electrode material layer, the mass percentage content A of the positive electrode active material is 95.4%, and the mass percentage content B of the first compound is 0.6%.

[0101] <Preparation of negative electrode sheet>

[0102] Artificial graphite is used as the negative electrode active material, mixed with styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 97.7:1.2:1.1, and then deionized water is added. The mixture is stirred thoroughly to form a uniform negative electrode slurry, wherein the solid content of the negative electrode slurry is 50wt%. The negative electrode slurry is coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. The above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Then, after drying under vacuum conditions at 120°C for 12 hours, the negative electrode sheet with a specification of 78mm×875mm is obtained by cold pressing, cutting and slitting. Among them, the coating weight of the negative electrode material layer during coating is 0.14g / 1540.25mm 2 The compaction density of the negative electrode material layer after cold pressing is 1.75g / cm 3 .

[0103] <Preparation of Electrolyte>

[0104] In a dry argon environment, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and propyl propionate (PP) are mixed in a mass ratio of 1:1:1:1 to obtain a base solvent, and then the second compound ethylene sulfate and the third compound methylene methane disulfonate (MMDS) are added, dissolved and fully stirred, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Among them, based on the mass of the electrolyte, the mass percentage content of LiPF6 is 1.15%, the mass percentage content C of the second compound ethylene sulfate is 0.1%, the mass percentage content D of the third compound methylene methane disulfonate is 0.1%, and the balance is the base solvent.

[0105] <Diaphragm>

[0106] A 5 μm thick polyethylene (PE) porous polymer film was used as the separator.

[0107] <Preparation of lithium-ion batteries>

[0108] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrodes to play an isolating role. Then they are wound, the pole ears are welded, and placed in the outer packaging foil aluminum-plastic film. The electrolyte is injected, and after vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack lithium-ion battery is obtained.

[0109] Example 1-2 to Example 1-15

[0110] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. When the mass percentage B of the first compound changes, the mass percentage A of the positive electrode active material changes accordingly, and the mass percentages of the two conductive agents and the positive electrode binder remain unchanged.

[0111] Examples 1-16

[0112] In addition to lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) is doped with the metal element Mg, and the mass percentage of the metal element Mg is 0.015% based on the residual mass of the lithium nickel cobalt manganese oxide minus the metal element Mg, that is, the doping amount of the metal element Mg is 0.015%, and based on the mass of the positive electrode material layer, the mass percentage of the positive electrode active material remains unchanged, and the rest is the same as Example 1-1.

[0113] Examples 1-17

[0114] In addition to lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.1 Al 0.1O2) is doped with metal element Zr, and the mass percentage of metal element Zr based on the residual mass of lithium nickel cobalt aluminum oxide minus the metal element Zr is 0.01%, that is, the doping amount of metal element Zr is 0.01%, and based on the mass of the positive electrode material layer, the mass percentage of the positive electrode active material remains unchanged, and the rest is the same as Example 1-1.

[0115] Examples 1-18

[0116] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0117] Example 2-1

[0118] Except for preparing the electrolyte according to the following steps, the rest is the same as Example 1-1.

[0119] <Preparation of Electrolyte>

[0120] In a dry argon environment, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and propyl propionate (PP) are mixed in a mass ratio of 1:1:1:1 to obtain a base solvent, and then the second compound, vinyl sulfate, is added, dissolved and fully stirred, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 1.15%, the mass percentage of the second compound vinyl sulfate C is 0.05%, and the remainder is the base solvent.

[0121] Example 2-2 to Example 2-6

[0122] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 2-1. When the mass percentage of the second compound changes, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of the lithium salt LiPF6 remains unchanged.

[0123] Embodiment 2-7

[0124] Except for preparing the electrolyte according to the following steps, the rest is the same as Example 1-1.

[0125] <Preparation of Electrolyte>

[0126] In a dry argon environment, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and propyl propionate (PP) are mixed at a mass ratio of 1:1:1:1 to obtain a base solvent, and then a third compound methylene disulfonate (MMDS) is added, dissolved and fully stirred, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 1.15%, the mass percentage of the third compound methylene disulfonate D is 0.05%, and the remainder is the base solvent.

[0127] Example 2-8 to Example 2-12

[0128] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 2-7. When the mass percentage of the second compound changes, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of the lithium salt LiPF6 remains unchanged.

[0129] Example 2-13

[0130] Except for preparing the electrolyte according to the following steps, the rest is the same as Example 1-1.

[0131] <Preparation of Electrolyte>

[0132] In a dry argon environment, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and propyl propionate (PP) were mixed at a mass ratio of 1:1:1:1 to obtain a base solvent, and lithium salt LiPF6 was added after sufficient stirring, and the electrolyte was obtained after mixing evenly. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 1.15%, and the balance is the base solvent.

[0133] Comparative Example 1

[0134] Except that the first compound is not added in <Preparation of Positive Electrode Plate>, the mass percentage A of the positive electrode active material changes accordingly, and the mass percentages of the two conductive agents and the positive electrode binder remain unchanged, the rest is the same as Example 1-1.

[0135] Comparative Example 2

[0136] Except that the first compound vinyl phosphate is replaced by methyl phosphate in <Preparation of positive electrode sheet>, the rest is the same as Example 1-1.

[0137] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.

[0138] Table 1

[0139] Note: “ / ” in Table 1 indicates no relevant preparation parameters.

[0140] It can be seen from Examples 1-1 to 1-18 and Comparative Examples 1 to 2 that by adding the first compound to the positive electrode material layer, the positive electrode material layer at 1150 cm -1 ±10cm -1 , and 1085cm -1 ±10cm -1 、1600cm -1 ±10cm -1 、1640cm -1 ±10cm -1 or 1500cm -1 ±10cm -1 There are infrared characteristic peaks at any two places in the , the first efficiency of the lithium-ion battery is high, the thickness expansion rate is small at high temperature, the DCR value is low at 50% state of charge, and the capacity retention rate is high at high temperature, and the hot box pass rate is high, indicating that the lithium-ion battery has good high-temperature cycle performance, taking into account low-temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium-ion battery are high. In Comparative Example 1, there is no characteristic peak within the scope of this application in the positive electrode material layer during infrared testing, and there is only one characteristic peak within the scope of this application in the positive electrode material layer during infrared testing in Comparative Example 2. At this time, the first efficiency of the lithium-ion battery in Comparative Examples 1 and Comparative Examples 2 is low, the thickness expansion rate is large at high temperature, the DCR value is high at 50% state of charge, and the capacity retention rate is low at high temperature, and the hot box pass rate is low, indicating that the lithium-ion battery cannot simultaneously take into account high-temperature cycle performance, low-temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium-ion battery are poor, and the thermal safety performance of the lithium-ion battery is low. The lithium ion batteries in Examples 1-1 to 1-18 have good high-temperature cycle performance, taking into account both low-temperature performance and impedance performance, and the lithium ion batteries have good thermal safety performance.

[0141] The content B of the first compound usually affects the high temperature cycle performance, low temperature performance, impedance performance and thermal safety performance of the lithium ion battery. It can be seen from Examples 1-1, 1-5 to 1-9 that when the content B of the first compound is adjusted within the scope of this application, the initial efficiency of the lithium ion battery is high, the thickness expansion rate is small at high temperature, the DCR value is low at 50% charge state, and the capacity retention rate is high at high temperature, and the hot box pass rate is high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the thermal safety performance of the lithium ion battery is good.

[0142] The type of positive electrode active material usually affects the high temperature cycle performance, low temperature performance, impedance performance and thermal safety performance of lithium ion batteries. It can be seen from Examples 1-1, 1-10 to 1-15 that when the positive electrode active material within the scope of this application is selected, the initial efficiency of the lithium ion battery is higher, the thickness expansion rate is smaller at high temperature, the DCR value is lower at 50% charge state, and the capacity retention rate is higher at high temperature, and the hot box pass rate is higher, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium ion battery are higher, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the thermal safety performance of the lithium ion battery is better.

[0143] The relationship between A, x and B usually affects the high temperature cycle performance, low temperature performance, impedance performance and thermal safety performance of lithium ion batteries. It can be seen from Examples 1-1 to 1-15 that when A, x and B satisfy the relationship of the present application, the initial efficiency of the lithium ion battery is high, the thickness expansion rate is small at high temperature, the DCR value is low at 50% charge state, and the capacity retention rate is high at high temperature, and the hot box pass rate is high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the thermal safety performance of the lithium ion battery is good.

[0144] The type of M1 or M2 usually affects the high temperature cycle performance, low temperature performance, impedance performance and thermal safety performance of the lithium ion battery. It can be seen from Example 1-1, Example 1-16 to Example 1-17 that when M1 or M2 within the scope of this application is selected, the initial efficiency of the lithium ion battery is higher, the thickness expansion rate is smaller at high temperature, the DCR value is lower at 50% charge state, and the capacity retention rate is higher at high temperature, and the hot box pass rate is higher, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium ion battery are higher, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the thermal safety performance of the lithium ion battery is better.

[0145] Table 2

[0146] “ / ” in Table 2 indicates no relevant preparation parameters.

[0147] The type and content of the second compound usually affect the high temperature cycle performance, low temperature performance, impedance performance and thermal safety performance of the lithium ion battery. It can be seen from Examples 1-1, 2-1 to 2-6, and 2-13 that when the electrolyte includes the second compound and the content of the second compound is within the scope of this application, the initial efficiency of the lithium ion battery is high, the thickness expansion rate is small at high temperature, the DCR value is low at 50% charge state, and the capacity retention rate is high at high temperature, and the hot box pass rate is high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the thermal safety performance of the lithium ion battery is good.

[0148] The type and content of the third compound usually affect the high temperature cycle performance, low temperature performance, impedance performance and thermal safety performance of the lithium ion battery. It can be seen from Examples 1-1, 2-7 to 2-13 that when the electrolyte includes the third compound and the content of the third compound is within the scope of this application, the initial efficiency of the lithium ion battery is high, the thickness expansion rate at high temperature is small, the DCR value at 50% charge state is low, and the capacity retention rate at high temperature is high, and the hot box pass rate is high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good high temperature cycle performance, taking into account low temperature performance and impedance performance, and the thermal safety performance of the lithium ion battery is good.

[0149] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0150] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0151] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, wherein the positive electrode material layer comprises a positive electrode active material and a first compound, wherein the first compound comprises at least one of vinyl phosphate, allyl phosphate, vinylidene phosphate, diallyl phosphate, styrene phosphate, diphenyl phosphate or distyrene phosphate, and the infrared spectrum of the positive electrode material layer is 1150cm -1 ±10cm -1 , and 1085cm -1 ±10cm -1 、1600cm -1 ±10cm -1 、1640cm -1 ±10cm -1 or 1500cm -1 ±10cm -1 There are infrared characteristic peaks at any two locations.

2. The positive electrode sheet according to claim 1, wherein: Based on the mass of the positive electrode material layer, the mass percentage of the first compound is B, and 0.1%≤B≤3%.

3. The positive electrode sheet according to claim 2, wherein: 0.1%≤B≤1%。 4. The positive electrode sheet according to claim 1, wherein: The positive electrode active material includes LiNi x Co y M 1-x-y O2, 0.6≤x≤1.0, 0≤y≤0.4, M is Al or Mn.

5. The positive electrode sheet according to claim 4, wherein: Based on the mass of the positive electrode material layer, the mass percentage of the positive electrode active material is A, and the mass percentage of the first compound is B; A, x and B satisfy: B=k×A×x, 93%≤A≤95.9%, 0.6≤x≤0.9, 0.001792≤k≤0.03475.

6. The positive electrode sheet according to claim 4, which satisfies at least one of the following characteristics: (1) The positive electrode active material includes lithium nickel cobalt manganese oxide, the lithium nickel cobalt manganese oxide includes a metal element M1, and the metal element M1 includes at least one of Al, Zr, Mg, Ba or Ti; (2) The positive electrode active material includes lithium nickel cobalt aluminum oxide, the lithium nickel cobalt aluminum oxide includes a metal element M2, and the metal element M2 includes at least one of Zr, Mg, Ba, or Ti. 7 . A secondary battery comprising a negative electrode sheet, a separator, an electrolyte, and the positive electrode sheet according to claim 1 .

8. The secondary battery according to claim 7, wherein The electrolyte includes a second compound, the second compound includes at least one of a cyclic sulfate ester compound or a cyclic carbonate ester compound, the cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate or methyl vinyl sulfate, and the cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate or fluoroethylene carbonate; based on the mass of the electrolyte, the mass percentage of the second compound is C, 0.05%≤C≤3%.

9. The secondary battery according to claim 7, wherein The electrolyte includes a third compound, and the third compound includes at least one of methylene methanedisulfonate, vinylene carbonate, ethyl methyl carbonate or methyl propyl carbonate. Based on the mass of the electrolyte, the mass percentage of the third compound is D, 0.05%≤D≤2%. 10 . An electronic device comprising the secondary battery according to claim 7 .

Citation Information

Patent Citations

  • Positive pole piece, secondary battery and electronic device

    CN116111044A

  • Phosphate ester organic matter intercalated vanadium pentoxide positive electrode composite material as well as preparation method and application thereof

    CN116314653A

  • Positive plate and battery

    CN119069639A